Perception of in-school adolescents about adolescent-friendly characteristics of healthcare services received in Ibadan metropolis, Nigeria (2019)
Introduction: Adolescence was previously assumed to be a diseases free stage of life. It is however now known that adolescents are not only involved in risky health behaviours but they also have their own share of health problems that other age groups face. The adolescent-friendly model helps to create adolescent-responsive health systems, Nigeria currently has no country-specific report on the adolescent friendly characteristics of the health services rendered to her adolescents. This study identified various health problems for which in-school adolescents in Ibadan North- East Local Government Area sought healthcare and determined their perception of received healthcare services with regards to its “adolescent-friendliness”. Methods: This was a school-based cross-sectional study that utilized quantitative method of data collection. A multi-stage systematic random sampling technique was employed to select 500 students for school survey. Self-administered, semi structured questionnaire was used to collect data. Descriptive statistics and Chi-square test at =0.05 were used for data analysis. Results: Perceived malaria (52.4%), acne (36.2%), menstrual pain (17.0%) and depression (3.0%) were the common health problems adolescents sought health care for. Majority of the adolescents perceived the health services received as being adolescent-friendly. These health services were perceived to be accessible by (87%), acceptable by (93.2%), appropriate by (81.4%), effective by (91.4%), and equitable by (82.2%) of the respondents. Adolescents who sought mental care perceived least adolescent-friendliness of received healthcare services. Conclusion: Adolescents in Ibadan currently view received health services as adolescent-friendly. However, the management of mental health problems in adolescents should incorporate adolescent friendly elements entrenched at every level of the health system.